2015
DOI: 10.1002/cssc.201403275
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Investigation of Free Radicals in Bio‐Oil and their Potential Role in Condensed‐Phase Polymerization

Abstract: We report on the quantitative analysis of free radicals in bio-oils produced from pyrolysis of cellulose, organosolv lignin, and corn stover by EPR spectroscopy. Also, we investigated their potential role in condensed-phase polymerization. Bio-oils produced from lignin and cellulose show clear evidence of homolytic cleavage reactions during pyrolysis that produce free radicals. The concentration of free radicals in lignin bio-oil was 7.5×10(20)  spin g(-1), which was 375 and 138 times higher than free-radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 50 publications
0
59
0
Order By: Relevance
“…It postulated that these radicals could possibly be oligosaccharides in nature, given the fact that a radical in fifth position in a glucose ring is stabilized by the adjacent alkyl group and oxygen atom. This study provides an evidence for free‐radical generation during homolytic cleavage of glycosidic bonds leading to the formation of stable free‐radicals and decarbonylation of monomeric units which result in the formation of CO (Kim et al, ).…”
Section: Mechanistic and Intrinsic Kinetic Studies Of Biomass Pyrolysismentioning
confidence: 87%
“…It postulated that these radicals could possibly be oligosaccharides in nature, given the fact that a radical in fifth position in a glucose ring is stabilized by the adjacent alkyl group and oxygen atom. This study provides an evidence for free‐radical generation during homolytic cleavage of glycosidic bonds leading to the formation of stable free‐radicals and decarbonylation of monomeric units which result in the formation of CO (Kim et al, ).…”
Section: Mechanistic and Intrinsic Kinetic Studies Of Biomass Pyrolysismentioning
confidence: 87%
“…A recent study by Kim et al showed that the majority of radicals contained in pyrolysis oil from wood are the products of lignin pyrolysis. [22] However, it seems that those radicals are stable and do not influence the stability of the liquid obtained after pyrolysis towards repolymerization, at least on the short term. Catalytic/non-catalytic pyrolysis of lignin comprises a very complex set of reactions due to the wide variety of bonds and monomers in the lignin matrix.…”
Section: Fast Pyrolysis Chemistrymentioning
confidence: 99%
“…Free radicals have been detected in various conditions during the pyrolysis of lignin and its model compounds in the gas phase, 11,12 bio-oil 13,14 and biochar media. 16 Kibet et al .…”
Section: Introductionmentioning
confidence: 99%